Clinical decision impact of HER2DX, an algorithm-powered genomic diagnostic in early-stage HER2-positive breast cancer: results from a prospective real-world study - Martínez-Sáez, O.; Tapia, M.; Marín-Aguilera, M.; Hernández-Illán, E.; Tébar, C.; Martinez-Puchol, A.I.; Jares, P.; Marín-Liébana, S.; Magro, A.; Puig-Butille, J.A.; Palomar, L.; Sanfeliu, E.; et al. (ESMO Real World Data and Digital Oncology, 2025)
HER2DX is a clinically available genomic assay that provides prognostic (relapse risk score), predictive [pathological complete response (pCR) likelihood score], and ERBB2 expression data in stage I-III human epidermal growth factor receptor 2 (HER2)-positive breast cancer (BC). This real-world study evaluated its clinical impact. This prospective study enrolled newly diagnosed patients with stage I-III HER2-positive BC across 12 hospitals in Spain (November 2021-September 2024). Thirty-four oncologists ordered HER2DX and completed questionnaires before and after receiving results to assess treatment changes (primary objective). Secondary objectives included evaluating the HER2DX pCR likelihood score association with pCR, test turnaround time, changes in physician confidence regarding treatment decisions, and cost-effectiveness. Among 297 recruited patients, 48.1% (95% confidence interval 42.5% to 53.7%) experienced treatment adjustments after HER2DX. Within these cases, 73.5% involved reduced treatment intensity, 24.5% involved increased treatment intensity, and the remaining cases (2.0%) involved mixed adjustments. Of the cases with reduced treatment intensity, 56.2% had a reduction in chemotherapy intensity, 26.7% had a reduction in anti-HER2 therapy, and 17.1% in both. Among the 182 patients with available pathological data at surgery, the pCR likelihood score was a significant predictor of pCR (P < 0.001). In 69 patients with pCR-high disease, less intensive treatment achieved similar pCR rates compared with multi-agent chemotherapy (81.5% versus 69.0%; odds ratio = 1.97, P = 0.256). Physician confidence improved (P < 0.001) and the estimated total cost savings, including direct drug costs, vein access devices, and HER2DX costs, amounted to €98 031. HER2DX impacts clinical management in stage I-III HER2-positive BC by supporting treatment adjustments, enhancing physician confidence, maintaining pCR rates, and reducing health care costs. •HER2DX assay led to treatment adjustments in nearly half of early-stage HER2-positive cases, mainly through de-escalation.•The HER2DX pCR likelihood score was a significant predictor of pCR outcomes.•HER2DX pCR-high patients had similar pCR rates with paclitaxel and dual anti-HER2 blockade as with multi-agent chemotherapy.•HER2DX results enhanced physician confidence in treatment decisions.•HER2DX reduced health care costs by minimizing expensive therapies and associated medical resources.